Status of diagnostic approaches to AQP4-IgG seronegative NMO and NMO/MS overlap syndromes - Juryńczyk, M; Weinshenker, B; Akman-Demir, G; Asgari, N; Barnes, D; Boggild, M; Chaudhuri, A; D’hooghe, M; Evangelou, N; Geraldes, R; Illes, Z; Jacob, A; et al. (Springer-Verlag, 2015)
Distinguishing aquaporin-4 IgG(AQP4-IgG)-negative neuromyelitis optica spectrum disorders (NMOSD) from opticospinal predominant multiple sclerosis (MS) is a clinical challenge with important treatment implications. The objective of the study was to examine whether expert clinicians diagnose and treat NMO/MS overlapping patients in a similar way. 12 AQP4-IgG-negative patients were selected to cover the range of clinical scenarios encountered in an NMO clinic. 27 NMO and MS experts reviewed their clinical vignettes, including relevant imaging and laboratory tests. Diagnoses were categorized into four groups (NMO, MS, indeterminate, other) and management into three groups (MS drugs, immunosuppression, no treatment). The mean proportion of agreement for the diagnosis was low (p o = 0.51) and ranged from 0.25 to 0.73 for individual patients. The majority opinion was divided between NMOSD versus: MS (nine cases), monophasic longitudinally extensive transverse myelitis (LETM) (1), acute disseminated encephalomyelitis (ADEM) (1) and recurrent isolated optic neuritis (RION) (1). Typical NMO features (e.g., LETM) influenced the diagnosis more than features more consistent with MS (e.g., short TM). Agreement on the treatment of patients was higher (p o = 0.64) than that on the diagnosis with immunosuppression being the most common choice not only in patients with the diagnosis of NMO (98 %) but also in those indeterminate between NMO and MS (74 %). The diagnosis in AQP4-IgG-negative NMO/MS overlap syndromes is challenging and diverse. The classification of such patients currently requires new diagnostic categories, which incorporate lesser degrees of diagnostic confidence. Long-term follow-up may identify early features or biomarkers, which can more accurately distinguish the underlying disorder.